(untitled) (The Review of Diabetic Studies, 2025)
Digital health education platforms have emerged as powerful tools for promoting lifestyle modification and preventing chronic diseases, particularly when integrated into primary care and led by multidisciplinary clinical teams. Family physicians and nursing teams are uniquely positioned to deliver patient-centered digital education due to their longitudinal relationships with patients and central role in preventive care. This review examines the effectiveness of digital health education platforms supported by medical informatics and led collaboratively by family physicians and nurses in influencing lifestyle behaviors such as physical activity, diet, smoking cessation, and medication adherence. The paper explores how informatics-driven personalization, remote monitoring, and data integration enhance preventive interventions and improve outcomes in chronic disease prevention. Evidence suggests that digitally enabled, team-based educational models can significantly improve patient engagement, self-management, and risk factor control when aligned with primary care workflows and supported by appropriate technological infrastructure.